2015
DOI: 10.1007/s13318-015-0272-7
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetic study of patchouli alcohol after a single oral administration of patchouli alcohol or patchouli oil in rats

Abstract: Pogostemonis herba is used in traditional Chinese medicine to remove dampness, relieve sunstroke, stop vomiting and increase appetite. Patchouli alcohol, an ingredient in pogostemonis herba, has the potential to treat inflammation as well as bacterial and fungal infections. The essential oil of pogostemonis herba (patchouli oil) is commonly given orally in clinical settings; however, no pharmacokinetic studies have examined its oral administration. The goal of this study was to investigate the pharmacokinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…PA, PO, and β-PAE compose of 39%, 8.9%, and 3.0% of PAO, respectively (van Beek and Joulain, 2018). These components of PC exhibited common as well as unique pharmaceutical activities (Li et al, 2014; Zhang et al, 2016a; Zhang et al, 2016b). For example, reports showed that PEO, PA, PO, and β-PAE possessed anti-inflammation, anti-oxidant, anti-cancer, immunomodulation in cellular and animal studies (Li et al, 2011; Liao et al, 2013; Jeong et al, 2013; Dechayont et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…PA, PO, and β-PAE compose of 39%, 8.9%, and 3.0% of PAO, respectively (van Beek and Joulain, 2018). These components of PC exhibited common as well as unique pharmaceutical activities (Li et al, 2014; Zhang et al, 2016a; Zhang et al, 2016b). For example, reports showed that PEO, PA, PO, and β-PAE possessed anti-inflammation, anti-oxidant, anti-cancer, immunomodulation in cellular and animal studies (Li et al, 2011; Liao et al, 2013; Jeong et al, 2013; Dechayont et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The agarwood plays a role in traditional Chinese medicine (TCM) and a large amount of it is also being consumed by distillation to obtain an essential oil [15]. On the other hand, Pogostemonis Herba is the aerial part of dried Pogostemon cablin (Blanco) and it also plays a vital role in TCM for the treatment of various problems such as to remove dampness, relieve sunstroke, stop vomiting and increase appetite [16]. Patchouli oil is the essential oil of pogostemonis Herba, and it has been widely used by traditional Chinese physicians to treat a wide array of medical conditions such as common cold, nausea, diarrhoea, headache and fever since time memorial.…”
Section: Introductionmentioning
confidence: 99%
“…and 17.82±9.29 h (100 mg/kg, i.g.) detected in rats (58). PA is metabolized in the liver and kidney, and two hydroxylated metabolites have been demonstrated in the liver of rabbits (59), and one carboxylate metabolite of PA has been identified in rat urine (60).…”
mentioning
confidence: 99%